Asimetrías pendientes de resolver - López García, Irene María (2022)
In Spain, the role of women within trade unions is little known. The purpose of this article is to describe the asymmetrical position of many women with respect to that of men in different facets of the life trajectory, that is, in the reproductive, productive and trade union work. It particularly analyzes the expressions of these inequalities in women who opted for professions in the field of social welfare and trade unionism, in the specific areas of health, education and social services. Traditionally feminized spaces and professions, in which their equivalence is not shown in the affiliation and leadership of trade union organizations. With the intention of understanding these manifestations, life history is used under the qualitative approach, a technique that allows transcending individual narratives to a collective experience. During the analysis, in which their biographies are traversed from domestic to professional places, it is observed how in the exercise of their union action converge those dynamics that have been legitimizing, over time, this gender differentiation. These are reiterated both in their formulas of internal trade union organization and in their participation strategies on employment and the labor market.